“Few things in life are easy and worth doing”: how the bi-directional relationships between meaningful work and work-related stress can both help and hinder wellbeing - Annison, Jess; Davidson, Adam (Frontiers in Psychology, 2023)
Introduction Meaning is a key part of psychological wellbeing, and the benefits of meaningful work are widely acknowledged. Many people seek meaning from their work, and some organizations aim to facilitate this through interventions. In parallel, work-related stress has become a significant occupational risk. This study seeks to understand the perspectives of those who find their work to be both meaningful and stressful, and to explore the relationships between these concepts. Methods Eleven women and six men, aged 34–61, primarily based in the UK, from the private, public, and third sectors were interviewed about their experiences of meaning and stress in their work. Using a social constructivist grounded theory approach, data collection and analysis ran in parallel. Results Findings indicate that meaningful work and work-related stress are inherently connected, with bi-directional relationships that can support and hinder wellbeing. Meaningfulness can both alleviate and exacerbate stress, and stress can both reinforce and reduce meaningfulness. Meaningfulness and stress can even feel co-dependent, depending on how participants perceive and make sense of their experience. Discussion With many individuals seeking greater meaningfulness from their work, the results suggest that they— and their employers—would benefit from understanding more about the potential harmful effects of meaningfulness, including implications for stress and possible knock-on consequences for health and work.